Surfactant-Assisted Fabrication of Alumina-Doped Amorphous Silica Nanofiltration Membranes with Enhanced Water Purification Performances - Xianzheng Ma; Katarzyna Janowska; Vittorio Boffa; Debora Fabbri; Giuliana Magnacca; Paola Calza; Yuanzheng Yue (Nanomaterials, 2019)
Surfactant-templated 5 mol% Al2O3-doped silica membranes nanofiltration membranes were synthesized via the sol-gel method, and afterward, were optimized, and tested with respect to the permeability and rejection rate. The disordered silica network was stabilized by doping 5 mol% alumina. Tetraethyl orthosilicate and aluminum isopropoxide were used as the silica and alumina precursors, respectively. Cetyltrimethylammonium bromide (CTAB) was used not only as a pore-forming agent, but also to control the reaction rate of the aluminum isopropoxide, thus obtaining highly homogeneous materials. The results about filtration of model solutions showed that the optimized membranes are featured by both a relatively high water permeability (1.1−2.3 L·m−2·h−1 ·bar−1) and a high rejection for salts (74% for NaCl, and >95% for MgSO4 and Na2SO4) and organic pollutants (e.g., about 98% for caffeine). High rejection of divalent ions and organic molecules was also observed when a real wastewater effluent was filtered. The influence of the synthesis conditions on the membrane performance is discussed.